2022
DOI: 10.3390/ijms23158424
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chilling-Responsive Genes in Litchi chinensis by Transcriptomic Analysis Underlying Phytohormones and Antioxidant Systems

Abstract: Litchi (Litchi chinensis Sonn.) is an important subtropical and tropical evergreen fruit tree that is seriously affected by chilling stress. In order to identify genes that may be involved in the response to chilling in litchi, we investigate the physiological and biochemical changes under chilling stress and construct 12 RNA-Seq libraries of leaf samples at 0, 4, 8, and 12 days of chilling. The results show that antioxidant enzymes are activated by chilling treatments. Comparing the transcriptome data of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Structural equation model can effectively reveal the relationship between plant metabolic biological processes [36]. Partial least squares structural equation model (PLS-SEM) analysis based on RNA-Seq data clari ed the possible ways of litchi responding to cold storage [37]. PLS-SEM analysis showed that arbuscular mycorrhizal fungus enhances lateral root formation in Poncirus trifoliata [38].…”
Section: Introductionmentioning
confidence: 99%
“…Structural equation model can effectively reveal the relationship between plant metabolic biological processes [36]. Partial least squares structural equation model (PLS-SEM) analysis based on RNA-Seq data clari ed the possible ways of litchi responding to cold storage [37]. PLS-SEM analysis showed that arbuscular mycorrhizal fungus enhances lateral root formation in Poncirus trifoliata [38].…”
Section: Introductionmentioning
confidence: 99%